2004
DOI: 10.1038/sj.hdy.6800453
|View full text |Cite
|
Sign up to set email alerts
|

Two unlinked loci controlling the sex of blue tilapia (Oreochromis aureus)

Abstract: Sex determination in the blue tilapia (Oreochromis aureus) is thought to be a WZ-ZZ (female heterogametic) system controlled by a major gene. We searched for DNA markers linked to this major gene using the technique of bulked segregant analysis. We identified 11 microsatellite markers on linkage group 3 which were linked to phenotypic sex. The putative W chromosome haplotype correctly predicts the sex of 97% of male and 85% of female individuals. Our results suggest the W locus lies within a few centimorgans o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
156
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(165 citation statements)
references
References 39 publications
4
156
0
5
Order By: Relevance
“…In salmonids (male heterogamety), comparative mapping of sexlinked microsatellite markers has already shown that Arctic charr, brown trout, Atlantic salmon and rainbow trout have evolved different sex chromosomes (Woram et al, 2003). Sex-linked markers have been found in the Nile tilapia Oreochromis niloticus (XX/XY) and the blue tilapia O. aureus (ZW/ZZ) (Lee et al, 2004), and the putative sex chromosomes have been identified by synaptonemal complex analysis (for a review, Griffin et al, 2002). In the threespine stickleback, sequencing of X-and Y-specific bacterial artificial chromosome clones from the sex determination region revealed many sequence differences between X and neo-Y chromosomes .…”
Section: Transposable Elements and Speciationmentioning
confidence: 99%
“…In salmonids (male heterogamety), comparative mapping of sexlinked microsatellite markers has already shown that Arctic charr, brown trout, Atlantic salmon and rainbow trout have evolved different sex chromosomes (Woram et al, 2003). Sex-linked markers have been found in the Nile tilapia Oreochromis niloticus (XX/XY) and the blue tilapia O. aureus (ZW/ZZ) (Lee et al, 2004), and the putative sex chromosomes have been identified by synaptonemal complex analysis (for a review, Griffin et al, 2002). In the threespine stickleback, sequencing of X-and Y-specific bacterial artificial chromosome clones from the sex determination region revealed many sequence differences between X and neo-Y chromosomes .…”
Section: Transposable Elements and Speciationmentioning
confidence: 99%
“…In many actual applications (e.g., Daniels et al 1998;Moritz et al 2003;Lee et al 2004), however, the actual value of population allele frequencies is not relevant; instead the main concern is the relative frequencies of alleles between two or more populations. In this situation bias may not be a concern, and we can ask how well larger DNA pools detect differences in allelic composition between populations.…”
Section: Experiments 1-variance Componentsmentioning
confidence: 99%
“…Allelic association studies, analyses of spatial population structure and effective population size, and the estimation of genetic diversity can potentially be addressed with DNA pooling. Aspects of marker development, such as the screening of many loci for polymorphisms and for sex linkage (Lee et al 2004), should be amenable to DNA pooling. The possibility of pooling certain tissues directly, such as pooling eggs, blood samples, or groups of larvae, also merits consideration.…”
Section: Experiments 1-variance Componentsmentioning
confidence: 99%
See 2 more Smart Citations